Cerebrospinal Fluid Levels of Amyloid Precursor Protein Are Associated with Ventricular Size in Post-Hemorrhagic Hydrocephalus of Prematurity - Morales, Diego M. (PLoS One, 2015)
BACKGROUND: Neurological outcomes of preterm infants with post-hemorrhagic hydrocephalus (PHH) remain among the worst in infancy, yet there remain few instruments to inform the treatment of PHH. We previously observed PHH-associated elevations in cerebrospinal fluid (CSF) amyloid precursor protein (APP), neural cell adhesion molecule-L1 (L1CAM), neural cell adhesion molecule-1 (NCAM-1), and other protein mediators of neurodevelopment. OBJECTIVE: The objective of this study was to examine the association of CSF APP, L1CAM, and NCAM-1 with ventricular size as an early step toward developing CSF markers of PHH. METHODS: CSF levels of APP, L1CAM, NCAM-1, and total protein (TP) were measured in 12 preterm infants undergoing PHH treatment. Ventricular size was determined using cranial ultrasounds. The relationships between CSF APP, L1CAM, and NCAM-1, occipitofrontal circumference (OFC), volume of CSF removed, and ventricular size were examined using correlation and regression analyses. RESULTS: CSF levels of APP, L1CAM, and NCAM-1 but not TP paralleled treatment-related changes in ventricular size. CSF APP demonstrated the strongest association with ventricular size, estimated by frontal-occipital horn ratio (FOR) (Pearson R = 0.76, p = 0.004), followed by NCAM-1 (R = 0.66, p = 0.02) and L1CAM (R = 0.57,p = 0.055). TP was not correlated with FOR (R = 0.02, p = 0.95). CONCLUSIONS: Herein, we report the novel observation that CSF APP shows a robust association with ventricular size in preterm infants treated for PHH. The results from this study suggest that CSF APP and related proteins at once hold promise as biomarkers of PHH and provide insight into the neurological consequences of PHH in the preterm infant.